Free Flap Reconstruction Outcomes among Elderly Patients. (2nd September 2014) - Goldman, Richard A.; Luginbuhl, Adam; Curry, Joseph; Cognetti, David M.; Krein, Howard D.; Heffelfinger, Ryan
Abstract : Objectives: Review a single institution's experience with free flap reconstruction of the head and neck in patients 80 years of age and older. Methods: A retrospective chart review was conducted of patients undergoing free tissue transfer for head and neck reconstruction in patients 80 years of age and older between 2008 and 2013 at a single academic tertiary care hospital. Main outcomes studied were free flap success rate, postoperative complications, discharge disposition, and length of hospital stay. Independent variables included age, type of reconstruction, and comorbid disease. Patients were stratified into high and low comorbidity groups using the Charlson Comorbidity Index, and associations with outcomes were analyzed. Results: A total of 65 patients 80 years of age or older were included in the review. There were 2 free flap failures with a success rate of 97%. Nine patients were 90 years of age or older. The average length of stay was 11 days. There were 11 (17%) flap‐related complications and 18 (28%) medical complications. There was no difference in medical or flap‐related complications between high and low comorbidity groups ( P =. 97 and P =. 18, respectively). Patients who experienced flap‐ related complications were more likely to also experience medical complications ( P =. 002). Conclusions: Free flap reconstruction in the head and neck remains a viable option in patients of advanced age. In our experience a comparable success rate with those reported in the literature among all patients has been achieved and the level of comorbid disease has not appeared to adversely affect outcomes.